2013
DOI: 10.1152/ajprenal.00393.2013
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the cAMP/PKA pathway induces UT-A1 urea transporter monoubiquitination and targets it for lysosomal degradation

Abstract: Regulation of urea transporter UT-A1 in the kidney is important for the urinary concentrating mechanism. We previously reported that activation of the cAMP/PKA pathway by forskolin (FSK) leads to UT-A1 ubiquitination, endocytosis, and degradation. In this study, we discovered that FSK-induced UT-A1 ubiquitination is monoubiquitination as judged by immunoblotting with specific ubiquitin antibodies to the different linkages of the ubiquitin chain. UT-A1 monoubiquitination induced by FSK was processed mainly on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…On the other hand, mono‐ or short ubiquitination are involved in the endocytosis of membrane proteins, followed by sorting to the lysosome (Su et al . ; Goo et al . ).…”
Section: N‐glycosylation Mutants Proceed Into the Lysosomal Degradatimentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, mono‐ or short ubiquitination are involved in the endocytosis of membrane proteins, followed by sorting to the lysosome (Su et al . ; Goo et al . ).…”
Section: N‐glycosylation Mutants Proceed Into the Lysosomal Degradatimentioning
confidence: 99%
“…The proteasome pathway is mediated by protein polyubiquitination. On the other hand, mono-or short ubiquitination are involved in the endocytosis of membrane proteins, followed by sorting to the lysosome (Su et al 2013;Goo et al 2015). The agonist-induced receptor internalization of GluA1, in part, mediates lysosomal degradation (Schwarz et al 2010).…”
Section: N-glycosylation Mutants Proceed Into the Lysosomal Degradatimentioning
confidence: 99%
“…Phosphorylation often regulates ubiquitination of proteins, thereby promoting their degradation [3941]. Several lines of evidence indicate that regulation of cell surface GABA B receptors by CaMKIIβ is conveyed by MIB2-mediated Lys-63-linked ubiquitination of GABA B1 .…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that FSK, the adenylyl cyclase stimulator often used for in vitro experiments to stimulate UT-A1 urea transport activity, can also promote UT-A1 ubiquitination and protein degradation, revealing the other side of UT-A1 phosphorylation by vasopressin or FSK (29,30). This observation has led to the hypothesis that phosphorylation could be required for UT-A1 ubiquitination.…”
Section: F76mentioning
confidence: 99%